Реализация экспериментальных исследований энергоэффективности одноковшового экскаватора через интеграцию вспомогательных виртуальных комплексов - V. V. Savinkin (Вестник СибАДИ, 2017)
The current stage of development of processes of modeling systems characterized by an increase of functional saturation. Modeling work processes excavator hydraulic drive is a complex hierarchical task, as in the performance of technological operations of the excavator is necessary to record and analyze a large number of factors and parameters, dynamically changing over time. The article reflected the description of the developed complex systems of the pilot studies shovel energy efficiency through the integration of support virtual systems, has a wide range of functionality and reduces the complexity of carrying out experimental research. Keywords. watching system, algorithm, resistance forces, kinematic couple.